Cobalt/Lewis Acid Catalysis for Hydrocarbofunctionalization of Alkynes via Cooperative C–H Activation - Wang, Chang-Sheng; Di Monaco, Sabrina; Thai, Anh Ngoc; Rahman, Md. Shafiqur; Pang, Benjamin Piaoxiang; Wang, Chen; Yoshikai, Naohiko (Journal of the American Chemical Society, 2020)
A catalytic system comprising a cobalt-diphosphine complex and a Lewis acid (LA) such as AIMe(3) has been found to promote hydrocarbofunctionalization reactions of alkynes with Lewis basic and electron-deficient substrates such as formamides, pyridones, pyridines and related azines, imidazo[1,2-a]pyridines, and azole derivatives through site-selective C-H activation. Compared with known Ni/LA catalytic systems for analogous transformations, the present catalytic systems not only feature convenient setup using inexpensive and bench-stable precatalyst and ligand such as Co(acac)(3) and 1,3-bis(diphenylphosphino)-propane (dppp) but also display distinct site-selectivity toward C-H activation of pyridone and pyridine derivatives. In particular, a completely C4-selective alkenylation of pyridine has been achieved for the first time. Meanwhile, the present catalytic system proved to promote exclusively C5-selective alkenylation of imidazo[1,2-a]pyridine derivatives. Mechanistic studies including DFT calculations on the Co/Al-catalyzed addition of formamide to alkyne have suggested that the reaction involves cleavage of the carbamoyl C-H bond as the rate-limiting step, which proceeds through a ligand-to-ligand hydrogen transfer (LLHT) mechanism leading to an alkenyl(carbamoyl)cobalt intermediate.